2021
DOI: 10.3390/agriculture11060520
|View full text |Cite
|
Sign up to set email alerts
|

The Survival of Family Farms: Socioemotional Wealth (SEW) and Factors Affecting Intention to Continue the Business

Abstract: This article addresses the problem of succession in family farms in a context of generational change. Family businesses are characterized by their long-term orientation and by having a positive effect through environmental goals that remain in place generation after generation. The general increase in average age among farmers is seen as a barrier to more sustainable land use, and the survival of family farming therefore depends on the availability of a successor in the family. Socioemotional wealth (hereafter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Therefore, married farm successors, due to their greater responsibilities, may hesitate to abandon their farming business. These results are in line with other studies [32,50].…”
Section: Results From the Occupational Choice Modelsupporting
confidence: 94%
“…Therefore, married farm successors, due to their greater responsibilities, may hesitate to abandon their farming business. These results are in line with other studies [32,50].…”
Section: Results From the Occupational Choice Modelsupporting
confidence: 94%
“…The questions in the questionnaire were formed by applying the concepts of the theory of vocational development of Super [14] and theory of occupational choice of Ginzberg [15]. In addition, some independent factors were also adopted from previous, similar studies reported in other countries [4,13,16,17]. However, the adoption of factors from other studies was based on the proper context that was deemed most suitable for Thailand's agricultural circumstances.…”
Section: Methodsmentioning
confidence: 99%
“…In Ghana, the receipt of federal services in the form of academic advice can help to boost the farming family's productivity and income [27,28]. Having a positive attitude towards the farming career can clearly strengthen the survival of family farms [4]. The reports of the International Fund for Agricultural Development [29] and the study reported in [30][31][32] reached the same conclusion, stating that the family's land size is one of the most important factors necessary to sustain the succession of family farming.…”
Section: Tool and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, emotional attachment to the farming family and its previous generations ensures the continuity of small‐scale family farms, albeit primarily as a part‐time lifestyle and less for economic profit (Hu & Gill, 2021, p. 411). Affective relationships with the family, early socialisation and involvement in farming foster succession (Bertolozzi‐Caredio et al., 2020; Plana‐Farran & Gallizo, 2021). On the other hand, transferors fear loss of control and identity—even in intra‐familial settings—which inhibits stepping aside (Cassidy et al., 2019; Chiswell, 2018; Conway et al., 2017, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%